2016
DOI: 10.1002/jib.376
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of technological approaches for reduction of methanol formation in plum wines

Abstract: Methanol is natural ingredient of alcoholic beverages and soft drinks; however, the products of its metabolic transformations (formaldehyde and formic acid) are toxic to humans. The aim of this research was to assess the application of different physico‐chemical treatments of pomace in order to find the most efficient method for reducing the methanol during fermentation with the least effect on the sensory properties of the wine. The following procedures were studied: addition of tannins in pomace, addition of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 18 publications
(30 reference statements)
0
14
0
Order By: Relevance
“…Further technological approaches for inactivation of methylesterase are thermosonication (ultrasound plus temperature at 70° led to 30% methanol reduction in plum wine) or use of microwaves (70 °C for 1 min led to 70% methanol reduction in plum wine). The authors indicated an additional nonthermal effect of both ultrasonication and microwaving with improved sensory properties of the product [ 41 ].…”
Section: Factors Influencing the Methanol Content Of Fruit Spiritsmentioning
confidence: 99%
“…Further technological approaches for inactivation of methylesterase are thermosonication (ultrasound plus temperature at 70° led to 30% methanol reduction in plum wine) or use of microwaves (70 °C for 1 min led to 70% methanol reduction in plum wine). The authors indicated an additional nonthermal effect of both ultrasonication and microwaving with improved sensory properties of the product [ 41 ].…”
Section: Factors Influencing the Methanol Content Of Fruit Spiritsmentioning
confidence: 99%
“…The acetaldehyde is one of the most important carbonyl compounds produced during fermentation, which at low levels contributes to fruity flavors, while high concentrations (200 mg/L) cause flatness in wines [36]. It was present in all analyzed jerkums.…”
Section: Volatile Compounds Of Fresh Plum Mustsmentioning
confidence: 97%
“…Further technological approaches for inactivation of methylesterase are thermosonication (ultrasound plus temperature at 70° led to 30% methanol reduction in plum wine) or use of microwaves (70°C for 1 min led to 70% methanol reduction in plum wine). The authors indicated an additional non-thermal effect of both ultrasonication and microwaving with improved sensory properties of the product [41].…”
Section: Inhibition Of Pectin Methylesterase By Sterilization Of Mashmentioning
confidence: 97%